Strengths Use for Tasks and Relationships in Organizations: Development and Validation of a Strengths Use Scale - Hai, Shenyang; Park, In-Jo (Frontiers in Psychology, 2022)
Individual character strengths have been increasingly valued, as they facilitate social functioning, well-being, and performance. However, little is known about how individuals use their strengths for important but distinct goals including task accomplishment and relationship maintenance in organizations. The purpose of this study is to develop and validate a Strengths Use Scale that can be used to measure the use of strengths for tasks and relationships in the workplace. For this purpose, we used the exploratory mixed method design and conducted a series of studies. In Study 1, we conducted an exploratory factor analysis to ensure the construct validity of the Strengths Use Scale on a sample of 187 employees. We found that the scale comprises two dimensions: strengths use for tasks and strengths use for relationships. In Study 2a, we verified the two-factor structure of the Strengths Use Scale using the confirmatory factor analysis on a separate sample of 213 employees. The results of Study 2b demonstrated that the scale has good measurement invariance across gender and age groups, on the sample of 205 employees. Moreover, strengths use for tasks and strengths use for relationships positively correlated with well-being and work engagement, and negatively correlated with turnover intention, supporting the criterion-related validity of the scale. In Study 3, a test–retest reliability analysis with a sample of 94 employees indicated that the scale has high reliability. Theoretical and practical implications of the findings are discussed.